Ethylene Continuous Rotating Detonation in optically accessible racetrack-like combustor. Issue 4 (3rd April 2019) - Peng, Haoyang; Liu, Weidong; Liu, Shijie
ABSTRACT: The optically accessible racetrack-like combustor designed for observation using high-speed photography is proposed. Series of Continuous Rotating Detonation (CRD) experiments with different combustor width, injection scheme, propellant and equivalence ratio are conducted. The operating domain results show that combustor width is a key factor for CRD realization. Ethylene CRD can be achieved on larger width combustor. Two propagation modes, namely, two waves in hetero-rotating mode and single wave mode, are achieved in the experiment. Based on the high-frequency pressures and high-speed photography images, the propagation characteristics and flowfield structures are discussed in detail. Some special flowfield structures are also observed and analyzed, including streak structure and downstream shock wave-ahead structure. The study will enhance the understanding of flowfield structure and flame dynamics of CRD Wave.